Exploring the Interplay between Environmental Leadership, Environmental Consciousness, and Environmental Awareness in Promoting Sustainable Entrepreneurship: Evidence from the Telecommunication Sector of Pakistan - Ali Shams, Haider; Ahmed, Sana; Ashraf, Hamid; Kiran, Aisha
This research investigates the interplay between Environmental Leadership (EL), Sustainable Entrepreneurship (SE), Environmental Consciousness (EC), and Environmental Awareness (EV) within the telecommunication sector of Pakistan. Utilizing Structural Equation Modelling (SEM) through Smart PLS, the study explores how EL influences SE directly and indirectly through EC, and how EV moderates this relationship. Data collected from 90 professionals in the sector were analysed to test the proposed hypotheses. Results indicate that EL positively impacts SE and EC, with EC mediating the EL-SE relationship. Additionally, EV was found to moderate the relationship between EL and SE, enhancing the positive effect of EL on SE when EV is high. The findings underscore the importance of integrating environmental consciousness and awareness into leadership strategies to foster sustainable entrepreneurship in the telecommunication sector.